Upaya peningkatan kunjungan penimbangan balita melalui program “Siaran Posyandu” di Wilayah Kerja Puskesmas Sumber Waras Kota Lubuklinggau - Ridawati, Indah Dewi; Setiyono, Imawan Eko; Kliwon, Kliwon (Nur Science Institute, 2025)
Detection of growth and development in infants, toddlers, and preschool children is an examination activity that identifies early deviations in their growth and development. By regularly and continuously weighing toddlers, abnormalities can be observed and identified as early as possible, allowing for timely follow-up. The percentage of toddler visits at the Sumber Waras Health Center is low, namely 63%. As many as 53.6% of mothers have low motivation in weighing toddlers. Most mothers (51.2%) do not routinely weigh their toddlers. Objective: to increase visits to the integrated health post through the “Posyandu Broadcast” program. Method: a survey of data collection on the number of target toddlers, cross-sector cooperation, and socialization to the community regarding the “posyandu broadcast” program, schedules, and the importance of attending the integrated health post through broadcasts around the Sumber Waras Health Center work area, and counseling on the importance of weighing toddlers. The results obtained were an increase in visits to the integrated health post. Suggestions for further community service include forming a mobile integrated health post that can reach the entire community.